In a single-blind, matched group design: branched-chain amino acid supplementation and resistance training maintains lean body mass during a caloric restricted diet - Dudgeon, W.; Kelley, E.; Scheett, T. (Journal of the International Society of Sports Nutrition, 2016)
Background: Athletes and active adults many times have the goal of improving/maintaining fitness while losing weight and this is best achieved by caloric restriction in combination with exercise. However, this poses a risk for lean tissue loss, which can limit performance. Thus, the purpose of this study was to determine the effectiveness of a branched-chain amino acid (BCAA) supplement, in conjunction with heavy resistance training and a carbohydrate caloric-restricted "cut diet" on body composition and muscle fitness. Methods: Seventeen resistance-trained males (21-28 years of age) were randomized to a BCAA group (n = 9) or a carbohydrate (CHO) group (n = 8) who both received their respective supplement during the 8 weeks of a prescribed body building style resistance training protocol. Subjects were prescribed a hypocaloric diet (based upon pre-intervention analysis) that was to be followed during the study. Results: The BCAA group lost fat mass (-0.05 ± 0.08 kg;p < .05) and maintained lean mass, while the CHO group lost lean mass (-0.90 ± 0.06 kg; p < .05) and body mass (-2.3 ± 0.7 kg; p < .05). Both groups increased 1RM squat, but the increase in the BCAA group (15.1 ± 2.2 kg; p < .05)was greater (P < 0.05) than the CHO group. The BCAA group increased 1RM bench press (7.1 ± 1.6 kg; P < 0.05), while the CHO group decreased strength (-3.7 ± 2.3 kg; P < 0.05). The only change in muscular endurance was an increase in repetitions to fatigue (5.3 ± 0.2; p < .05) in the CHO group. Conclusion: These results show that BCAA supplementation in trained individuals performing resistance training while on a hypocaloric diet can maintain lean mass and preserve skeletal muscle performance while losing fat mass.